2014
DOI: 10.1007/s00792-013-0622-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of poly-3-(hydroxybutyrate-co-hydroxyvalerate) by Haloferax mediterranei using rice-based ethanol stillage with simultaneous recovery and re-use of medium salts

Abstract: Haloferax mediterranei holds promise for competitive industrial-scale production of polyhydroxyalkanoate (PHA) because cheap carbon sources can be used thus lowering production costs. Although high salt concentration in production medium permits a non-sterile, low-cost process, salt disposal after process completion is a problem as current environmental standards do not allow total dissolved solids (TDS) above 2000 mg/l in discharge water. As the first objective of this work, the waste product of rice-based et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 26 publications
1
51
1
1
Order By: Relevance
“…Additionally, about 29 % of yeast extract, an expensive growth additive needed as nitrogenand phosphate source for efficient cultivation of the strain, can be replaced by cell debris from previous cultivations [64]. Similar strategies were followed by Bhattacharyya and colleagues [65], who used waste stillage from the rice-based ethanol production for Hfx. mediterannei mediated PHB production.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, about 29 % of yeast extract, an expensive growth additive needed as nitrogenand phosphate source for efficient cultivation of the strain, can be replaced by cell debris from previous cultivations [64]. Similar strategies were followed by Bhattacharyya and colleagues [65], who used waste stillage from the rice-based ethanol production for Hfx. mediterannei mediated PHB production.…”
Section: Discussionmentioning
confidence: 99%
“…Production of these valued compounds was described starting from carbon sources like glucose 16 , hydrolyzed lactose from dairy waste 9,10 , starchy residues 17,18 , vinasse 19 , rice-based ethanol stillage 20 , or glycerol from biodiesel production 21 . Already in 1995, the high potential of this organism to be implemented in "White Biotechnology", especially for bioplastic production, was discussed 22 , whereas only a few years ago, the application of the strain for PHA production explicitly from different agro-industrial waste streams was suggested by several authors 9,10,[17][18][19][20][21] . A comprehensive overview of the biotechnological potential of H. mediterranei and related halophilic species was provided by Quillaguamán and colleagues 23 .…”
Section: Biotechnological Potential Of the Strain Haloferax Mediterraneimentioning
confidence: 99%
“…Cheap carbon sources such as glycerol [89,90], rice bran [91], rice-based ethanol stillage [92], cheese whey [93], and olive mill wastewater (the effluent of the olive oil industry) have been tested using multistage processes [94,95] or only one-stage process ( …”
Section: Haloarchaea As Polyhydroxyalkanoate Producersmentioning
confidence: 99%